Indikator Keuangan dan Kepemilikan Keluarga: Kunci Prediksi Financial Distress Perusahaan - Nikke Yusnita Mahardini; Kodriyah; Santi Oktaviani; Atika Indriyani Putri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2025)
This study examines the influence of activity ratios, leverage, valuation, and family ownership on financial distress among manufacturing firms in Indonesia. This research highlights the importance of early detection of financial distress to prevent bankruptcy, which can have widespread effects on stakeholders. The study employs a quantitative method using secondary data from 107 companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The analysis is conducted using a discriminant model. The findings indicate that the ratios of Sales to Total Assets (STA), Market Value of Equity to Book Value of Total Liabilities (MVEBVTL), market capitalization, and family ownership can be used to predict corporate financial distress. The discriminant model applied has an accuracy rate of 82.4%. This study provides a significant contribution to identifying both financial and non-financial factors that affect the condition of financial distress, especially in family-owned businesses. Keywords: Activity Ratio; Leverage; Valuation; Family Ownership; and Financial Distress.